The association between carbon and nitrogen stable isotope ratios of human hair and hypertension - Song Vogue Ahn; Jong-Ku Park (BMC, 2023)
Abstract Background The relationship between stable isotope ratios and dietary protein sources has been reported. However, few studies have examined the effect of stable isotope ratios on metabolic risk in humans. We investigated whether the stable isotope ratios of carbon and nitrogen in human hair are associated with blood pressure and hypertension. Methods We conducted a cross-sectional study of 392 subjects (228 men and 164 women). Hair samples of the subjects were used for the measurement of stable isotope ratios of carbon (δ13C) and nitrogen (δ15N). Results The δ13C and δ15N values showed positive correlations with diastolic blood pressure in the subjects without antihypertensive medication. In the subjects without antihypertensive medication, the multivariable-adjusted odds ratio (95% confidence interval) for hypertension was 1.55 (1.04-2.30) per 1‰ increase in δ15N and 1.22 (0.86-1.73) per 1‰ increase in δ13C, respectively. However, in the subjects with antihypertensive medication, neither δ13C nor δ15N values showed a significant association with hypertension. Conclusions The stable isotopic ratio of nitrogen in scalp hair is independently associated with hypertension in subjects without antihypertensive medication. The hair δ15N value might be used as a surrogate marker to screen a high-risk population for hypertension.